EXCESS CASH HOLDINGS DAN KEPEMILIKAN INSTITUSIONAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Yessica Tria Christina; Erni Ekawati (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2014)
This research provides an empirical evidence about the effect of institutional ownerships as a proxy of information transparancy on excess cash holdings. Manufacture companies listed on BEI from years 2002 to 2011 are employed. The results show that the higher the proportion of institutional ownership, the lower the excess cash holdings. Informational transparancy, as one of the requirements of good corporate governance, can in fact lower the chance of aggrevating the manager’s behavior to practice excess cash holdings that can lower the company’s efficiency.